Satellite remote sensing reveals impacts from dam‐associated hydrological changes on chlorophyll‐a in the world's largest desert lake. (15th December 2019) - Tebbs, Emma J.; Avery, Sean T.; Chadwick, Michael A.
Abstract: We present an approach that uses satellite products to derive models for predicting lake chlorophyll from environmental variables, and for investigating impacts of changing environmental flows. Lake Turkana, Kenya, is the world's largest desert lake, and environmental flows from the Omo River have been modified since 2015 by the Gibe III dam in Ethiopia. Using satellite remote sensing, we have evaluated the influence of these altered hydrological patterns on large‐scale lake phytoplankton concentrations for the first time. Prior to dam completion, strong seasonal cycles and large spatial gradients in chlorophyll have been observed, related to natural fluctuations in the Omo River's seasonal discharge. During this period, mean lake chlorophyll showed a strong relationship with both river inflows and lake levels. Empirical models were derived which considered multiple hydro‐climatic drivers, but the best model for predicting chlorophyll‐a was a simple model based on Omo River discharge. Application of this model to data for 2015–2016 estimated that during the filling of Gibe III annual mean Lake Turkana chlorophyll declined by 30%. Future water management scenarios based on Gibe III operations predict reduced seasonal chlorophyll‐a variability, while irrigation scenarios showed marked declines in chlorophyll‐a depending on the level of abstraction. These changes demonstrate how infrastructure developments such as dams can significantly alter lake primary production. Our remote sensing approach is easy to adapt to other lakes to understand how their phytoplankton dynamics may be affected by water management scenarios.